PROTEÇÃO CONSTITUCIONAL À MORADIA E À PENHORA DO BEM DE FAMÍLIA: ASPECTOS RELATIVOS À (IN)CONSTITUCIONALIDADE DO RECENTE TEMA Nº 1.127 DO STF - Maraldi, Maricy; Thomaz Perez Reis Lobo, Mônica de Cássia (Revista da AJURIS, 2023)
CONSTITUTIONAL PROTECTION OF HOUSING AND LEVY OF EXECUTION OF FAMILY ASSETS: ASPECTS RELATED TO THE (UN)CONSTITUTIONALITY OF THE RECENT MATTER Nº 1.127 OF THE FEDERAL SUPREME COURT ÁREA(S): direito civil; direito constitucional. RESUMO: O presente artigo busca trazer uma reflexão sobre a recente tese fixada no âmbito do Supremo Tribunal Federal, por maioria de votos (Tema nº 1.127), no sentido da constitucionalidade da penhora do bem de família do fiador em contrato de locação comercial. A abordagem passa pela análise da “dignidade da pessoa humana” em seu aspecto patrimonial; a proteção constitucional conferida ao bem de família e a análise da eficácia civil dos direitos fundamentais, e em qual medida o recente Tema coaduna-se (ou não) com os valores constitucionais. ABSTRACT: This article sought to bring considerations to the recent thesis established within the scope of the Federal Supreme Court by majority vote (Matter nº 1.127), regarding the constitutionality of the levy of execution of the family asset guarantor in a commercial lease agreement. The approach went through the analysis the “dignity of the human person” in its proprietary aspect; the constitutional protection conferred to family assets and the examination of the civil effectiveness of fundamental rights, contemplating to what extent the recent matter is in line (or not) with constitutional values. PALAVRAS-CHAVE: bem de família; penhorabilidade; eficácia civil dos direitos fundamentais. KEYWORDS: family assets; levy of execution; civil effectiveness of fundamental rights. SUMÁRIO: Introdução; 1 Bem de família e o Tema nº 1.127 do STF; 2 Proteção constitucional à moradia: princípio da dignidade da pessoa humana e o mínimo existencial; 3 Eficácia civil dos direitos fundamentais e o protagonismo do Poder Judiciário; Conclusão; Referências. SUMMARY: Introduction; 1 Family property and Theme nº 1.127 of the Federal Supreme Court; 2 Constitutional protection of housing: principle of human dignity and the right to basic conditions of life; 3 Civil efficacy of fundamental rights and the role of the Judiciary; Conclusion; References.